2006
DOI: 10.1121/1.2184987
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the off-axis angle and the rotational movements of phonating sperm whales using a single hydrophone

Abstract: OATAO is an o pen ac cess re pository that c ollects th e work of To ulouse re searchers a nd makes it freely available over the web where possible.Any correspondence concerning this service should be sent to the repository

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…The reliability of this technique is, however, considerably complicated by the fact that the pulse structure of clicks is highly dependent on the aspect of the whale relative to the recorder ͑Zimmer et al., 2005b;Laplanche et al, 2006͒. Unless the recorder is on or near the anterior-posterior axis of the whale, then intermediate pulses can occur, making it hard to resolve the "true" IPI ͑Fig. 2͒.…”
Section: Introductionmentioning
confidence: 99%
“…The reliability of this technique is, however, considerably complicated by the fact that the pulse structure of clicks is highly dependent on the aspect of the whale relative to the recorder ͑Zimmer et al., 2005b;Laplanche et al, 2006͒. Unless the recorder is on or near the anterior-posterior axis of the whale, then intermediate pulses can occur, making it hard to resolve the "true" IPI ͑Fig. 2͒.…”
Section: Introductionmentioning
confidence: 99%
“…Other click components ͑resulting from further reflections in the head and other exit points͒ are also present ͑Møhl, 2001͒, but they are not required or considered here. Since the measured delay between the p0 and p1 pulses depends on the orientation of the whale ͑Zimmer et al., 2005a;Laplanche et al, 2006͒, it can be used to recover roll.…”
Section: Introductionmentioning
confidence: 99%
“…[8] have suggested that sperm whales would, at depth, make an asymmetric scan of the surrounding water and that during the search phase sperm whales would methodically scan a cone-shaped mass of water searching for prey. This scan would suggest that each sperm whale click is generated to aim in a specific direction at a specific range.…”
Section: Behavior Analysismentioning
confidence: 99%
“…level control: sperm whales would click slowly at a high source level and faster at a lower source level. In [8] the proposed echolocation model specifies that sperm whales would aim at closer targets while emitting clicks with lower source level at higher rhythmic rate, and aim at farther targets emitting clicks with higher source level and slower rhythmic rate. Finally, [9], [10] suggests that sperm whales move at constant heading and speed while hunting.…”
Section: Behavior Analysismentioning
confidence: 99%
See 1 more Smart Citation